Antioxidant/Pro-Oxidant Actions of Polyphenols From Grapevine and Wine By-Products-Base for Complementary Therapy in Ischemic Heart Diseases - Chedea, Veronica Sanda; Tomoiagǎ, Liliana Lucia; Macovei, Ştefan Octavian; Mǎgureanu, Dan Claudiu; Iliescu, Maria Lucia; Bocsan, Ioana Corina; Buzoianu, Anca Dana; Voşloban, Crinuţa Maria; Pop, Raluca Maria (Frontiers in Cardiovascular Medicine, 2021)
Grape pomace and grape seeds, by-products of the wine industry, and grapevine cane resulting from grapevine pruning are cheap matrices containing important amounts of polyphenols. While there is a continuous need of introducing new ways of these by-products valorization, we propose their use as a source of bioactive polyphenols for complementary therapy in ischemic heart diseases. As oxidative stress plays an important role in these diseases, by their antioxidant/pro-oxidant properties, these compounds, mainly flavan-3-ols, procyanidins, and resveratrol may counteract the damage of the oxidative stress. For instance, to some extent, the grape seed extract, considered as an antioxidant nutritive supplement, may have pro-oxidant activity as well, depending on dose, duration of administration, and other dietary components. In vitro studies confirm that the antioxidant activity of this extract might be mediated by pro-oxidant o-quinones and oxidation products of the polyphenols from grape and winery byproducts, indicating that quinones, as oxidation products, are involved in the modulation of the antioxidant/pro-oxidant balance at the cellular level in the case of catechin-type compounds, in the absence or presence of oxidative stress inducers. In vivo, studies indicate that a grape pomace-rich diet results in a significant increase of the total antioxidant status in the plasma, liver, spleen, and kidneys. Also, the administration of grape pomace shows antioxidant activity with positive effects on health. In this context, the present review aims to present the most recent research focused on the antioxidant/pro-oxidant actions of the bioactive polyphenols from grapevine and wine byproducts, in conditions of ischemic heart diseases as assessed in vitro or in vivo.